2011
DOI: 10.1073/pnas.1012464108
|View full text |Cite
|
Sign up to set email alerts
|

Masking the 5′ terminal nucleotides of the hepatitis C virus genome by an unconventional microRNA-target RNA complex

Abstract: Hepatitis C virus subverts liver-specific microRNA, miR-122, to upregulate viral RNA abundance in both infected cultured cells and in the liver of infected chimpanzees. These findings have identified miR-122 as an attractive antiviral target. Thus, it is imperative to know whether a distinct functional complex exists between miR-122 and the viral RNA versus its normal cellular target mRNAs. Toward this goal, effects on viral RNA abundance of mutated miR-122 duplex molecules, bound at each of the two target sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
297
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 264 publications
(307 citation statements)
references
References 27 publications
7
297
2
1
Order By: Relevance
“…Until recently, efficient HCV infectious culture systems were based on the genotype 2a isolate JFH1 in systems permitting studies in vitro and in vivo (Bukh, 2012;(nt 1-42; numbering according to genotype 2a isolate HC-J6, GenBank accession no. NC_009823) contains one stemloop structure (stem-loop I, SLI) (Honda et al, 1999), and two microRNA 122 (miR-122) binding sites (S1 and S2) (Henke et al, 2008;Jopling, 2008;Jopling et al, 2005;Machlin et al, 2011). It has been shown that the SLI is important for viral RNA replication (Friebe et al, 2001;Luo et al, 2003), and we demonstrated that it is essential for the viability of infectious HCV genotype 1-6 recombinants (Li et al, 2011a).…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…Until recently, efficient HCV infectious culture systems were based on the genotype 2a isolate JFH1 in systems permitting studies in vitro and in vivo (Bukh, 2012;(nt 1-42; numbering according to genotype 2a isolate HC-J6, GenBank accession no. NC_009823) contains one stemloop structure (stem-loop I, SLI) (Honda et al, 1999), and two microRNA 122 (miR-122) binding sites (S1 and S2) (Henke et al, 2008;Jopling, 2008;Jopling et al, 2005;Machlin et al, 2011). It has been shown that the SLI is important for viral RNA replication (Friebe et al, 2001;Luo et al, 2003), and we demonstrated that it is essential for the viability of infectious HCV genotype 1-6 recombinants (Li et al, 2011a).…”
Section: Introductionmentioning
confidence: 67%
“…1a) (Machlin et al, 2011). We previously found that deletion of the first nucleotide, A, of the J6 5¢UTR-NS2 /JFH1 recombinant could be repaired by addition of A or AC at the 5¢ terminus during virus replication in Huh7.5 cells, thus producing viruses with a variable length of 5¢E upstream of SLI (Li et al, 2011a, b).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations